Liquefaction Analysis Using Horizontal to Vertical Spectral Ratio in Arang Beach, Labuhan Ijuk, Sumbawa Area - Nurcahaya, Nurcahaya; Minardi, Suhayat; Zubaidah, Teti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Indonesia’s tectonic setting makes coastal areas highly vulnerable to seismic hazards, including liquefaction. This study aims to analyze the liquefaction potential in Arang Beach, Labuhan Ijuk, Sumbawa, using the Horizontal to Vertical Spectral Ratio (HVSR) method. Microtremor data were collected at 70 measurement points and processed using Geopsy through windowing, filtering, and HVSR analysis to obtain dominant frequency (f₀) and amplification factor (A₀), followed by inversion to estimate shear wave velocity (Vₛ), sediment thickness (h), and Poisson’s ratio (σ). The results show that f₀ ranges from 0.294–17.542 Hz and A₀ from 0.928–15.914, with low-frequency and high-amplification zones concentrated in the southern–western area, indicating thick, soft sediments. Vₛ values (63.486–712.48 m/s) further confirm the presence of very soft to hard subsurface layers, with high liquefaction susceptibility associated with low Vₛ, high σ, and thick sediments. These findings indicate that the southern–western part of the study area has the highest seismic vulnerability and liquefaction potential. This study concludes that HVSR is effective for identifying site effects and liquefaction-prone zones. The results provide a scientific basis for seismic microzonation, coastal spatial planning, and the development of earthquake-resistant infrastructure in vulnerable coastal regions.